Can you become one of us? A historical comparison of legal selection of 'assimilable' immigrants in Europe and the Americas. Issue 1 (2nd January 2018) - FitzGerald, David S.; Cook-Martín, David; García, Angela S.; Arar, Rawan
ABSTRACT: Pre-arrival integration tests used by European countries suggest discriminatory measures subtly persist in immigration laws. This paper draws on a comparison across the Americas and Europe to identify and explain historical continuities and discontinuities in 'assimilability' admissions requirements. We attribute legal shifts at the turn of the twenty-first century to the institutionalised delegitimisation of biological racism and the rise of permanent settlement immigration to Europe. Efforts to reduce Muslim immigration largely motivate contemporary European policies, but these policies test putative individual capacity to integrate rather than inferring it from a racial group categorisation, as did historical precedents in the Americas.